2010
DOI: 10.1007/s13157-010-0028-8
|View full text |Cite
|
Sign up to set email alerts
|

Restoration Response of Relict Broadleaf Marshes to Increased Water Depths

Abstract: Broadleaf marsh once covered much of the wetland landscape along the Kissimmee River in central Florida, USA, but is currently restricted to remnant portions of the channelized floodplain that have been subjected to much shallower depths. The initial phase of Kissimmee River restoration, which began in 1999, and a prior (1984)(1985)(1986)(1987)(1988)(1989)(1990) demonstration project increased water depths in several relict broadleaf marshes on the floodplain. Effects of restored water depth regimes on charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…This apparent inconsistency with prevailing flood pulse theory (Junk et al 1989) may be due to the duration and intensity of annual flood disturbances (Romme et al 1998) on the Kissimmee, which have been restored to reflect somewhat unique hydrologic regimes. However, plant species richness in the restored wet prairie was at least 50% higher than in restored broadleaf marsh (Toth 2010b), the dominant plant community on historic floodplain, and conforms with predicted patterns for lateral connectivity gradients in river corridors (Ward and Tockner 2001).…”
Section: Discussionsupporting
confidence: 77%
“…This apparent inconsistency with prevailing flood pulse theory (Junk et al 1989) may be due to the duration and intensity of annual flood disturbances (Romme et al 1998) on the Kissimmee, which have been restored to reflect somewhat unique hydrologic regimes. However, plant species richness in the restored wet prairie was at least 50% higher than in restored broadleaf marsh (Toth 2010b), the dominant plant community on historic floodplain, and conforms with predicted patterns for lateral connectivity gradients in river corridors (Ward and Tockner 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Research in the southern Kissimmee River floodplain has suggested that L. peruviana may be inhibiting reestablishment of BLM-BB. Results of ground monitoring from 1998 to 2008 of historically BLM-BB plots near PC21 which had not regained historic cover of BLM-BB (Toth 2010a) showed dominance by L. peruviana, which was interpreted by the author as possible suppression of BLM-BB by the invasive shrub. In another study, Toth (2010b) found that BLM-BB failed to attain dominance in plots on and near the backfilled canal east of MacArthur Impoundment between PC21 and PC32; here also, the author speculated that the presence of L. peruviana may be inhibiting establishment of BLM-BB.…”
Section: Discussionmentioning
confidence: 95%
“…Historical contingencies from early disturbances, the potential for alternative endpoints, and the successional timeframe for soil development belie assumptions that provide the basis for several myths that have clouded the science and practice of restoration ecology (Hilderbrand et al ). Mixed responses to the ongoing Kissimmee River restoration effort, including progress (Toth & van der Valk ; Colangelo ; Koebel et al ; Toth ) and shortcomings (Toth ; Cheek et al ; Spencer & Bousquin ), indicate elements of restoration projects with broad, ecosystem scale goals (e.g. ecological integrity) will have inconsistent temporal trajectories that need to be considered in evaluation and adaptive management plans (Suding ).…”
Section: Discussionmentioning
confidence: 99%